2020
DOI: 10.7554/elife.57626
|View full text |Cite
|
Sign up to set email alerts
|

Expression of different L1 isoforms of Mastomys natalensis papillomavirus as mechanism to circumvent adaptive immunity

Abstract: Although many high-risk mucosal and cutaneous human papillomaviruses (HPVs) theoretically have the potential to synthesize L1 isoforms differing in length, previous seroepidemiological studies only focused on the short L1 variants, co-assembling with L2 to infectious virions. Using the multimammate mouse Mastomys coucha as preclinical model, this is the first study demonstrating seroconversion against different L1 isoforms during the natural course of papillomavirus infection. Intriguingly, positivity with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 72 publications
3
18
0
Order By: Relevance
“…Green M: methionine upstream of the Wx7YLPP motif initiates L1 SHORT .Red M: upstream in-frame methionine of L1 LONG . Figure modified from ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Green M: methionine upstream of the Wx7YLPP motif initiates L1 SHORT .Red M: upstream in-frame methionine of L1 LONG . Figure modified from ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…For that purpose, 8-week-old virus-free Mastomys coucha (six animals per group) were vaccinated four times in biweekly intervals until week 6, followed by experimental MnPV infection at week 10 (outlined in Figure 2 ) and followed for up to 52 weeks (continued in Figure 4 ). Since our previous study showed that kinetics of seroconversion and specificity of antibodies against L1 LONG and L1 MIDDLE variants were similar ( 14 ), we only compared the impact of L1 LONG and L1 SHORT vaccination on subsequent viral challenge and skin tumor formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations